2012
DOI: 10.3354/meps09593
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure and biomagnification of mercury in an assemblage of deepwater chondrichthyans from southeastern Australia

Abstract: Stable isotope ratios of carbon (δ (wet mass, wm) with the highest concentrations correlated with increasing individual size and TP. Using published (TP and THg) data on low-mid trophic prey groups collected from the study area, THg biomagnification factors between selected predator−prey associations and trophic magnification factors (TMF) within various assemblage and community groupings were calculated. As an assemblage, deepwater elasmobranchs demonstrated moderate rates of THg biomagnification, as indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 58 publications
1
22
1
Order By: Relevance
“…of the sharks are also a significant determinant. In one of the only other studies examining several shark species simultaneously, δ 15 N better accounted for THg variation than did size in an assemblage of deepwater chondrichthyans from southeastern Australia (Pethybridge et al 2012). Due to low sample sizes for most species, however, those authors only examined overall THg-length relationships, which are likely weaker than species-specific relationships, as observed in our data.…”
Section: Ecological Factors Influencing Thg Levelsmentioning
confidence: 58%
See 1 more Smart Citation
“…of the sharks are also a significant determinant. In one of the only other studies examining several shark species simultaneously, δ 15 N better accounted for THg variation than did size in an assemblage of deepwater chondrichthyans from southeastern Australia (Pethybridge et al 2012). Due to low sample sizes for most species, however, those authors only examined overall THg-length relationships, which are likely weaker than species-specific relationships, as observed in our data.…”
Section: Ecological Factors Influencing Thg Levelsmentioning
confidence: 58%
“…Given CH 3 Hg biomagnification through aquatic food webs, it is expected that sharks feeding at a higher trophic position will have higher CH 3 Hg concentrations than those feeding lower in the food web. To date, a small number of studies have reported positive correlations between CH 3 Hg concentrations and trophic position, or nitrogen stable isotope ratios (δ 15 N) as a proxy for trophic position, in sharks (Cai et al 2007;Cresson et al 2014;McMeans et al 2010;Newman et al 2011;Pethybridge et al 2012). Additionally, recent studies have found correlations between shark CH 3 Hg tissue values and foraging depth or other habitat-use metrics, including carbon stable isotope ratios (δ 13 C) as a proxy for resource use, e.g., inshore benthic versus offshore pelagic (Choy et al 2009;Cossa et al 2012;McMeans et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Further investigation by comparative sampling in areas where similar surface currents do not exist, and/or through the use of stable isotope analysis (e.g. Pethybridge et al, 2012;Hussey et al, 2012), is recommended. (Castro, 2011;Compagno, 1984;McLaughlin and Morrissey, 2004;Russell et al, 1988).…”
Section: Resilience To Longline Capturementioning
confidence: 99%
“…Lipids are 13 C-depleted relative to proteins, and osmolytes that facilitate cellular 66 osmoconformation (Laxson et al, 2010), such as urea are 15 N-depleted relative to proteins, 67 such that higher lipid and urea concentrations result in artificially lower δ 13 Given these confounding factors, researchers must choose a suitable approach to 73 offset the biasing effects of lipids, for which three commonly published approaches are 74 preferred for sharks: 1. assume a negligible lipid content based on a low C:N ratio (< 3.4), 75 and present bulk data (Pethybridge et al, 2012); 2. perform chemical extraction, which may 76 additionally remove urea (Hussey et al, 2012b;Burgess and Bennett, 2017) or 3. 77 mathematically correct for lipids using models generated for teleost fishes (Reum et al, 78 2011).…”
Section: Introduction 50mentioning
confidence: 95%